EFEKTIVITAS JABATAN PEJABAT PELAKSANA TUGAS (PLT.) DALAM PENYELENGGARAAN PEMERINTAHAN - Triwahyuni, Dewi; Fuqoha, Fuqoha (Sawala : Jurnal Administrasi Negara, 2015)
In the government as an organization, it can not be separated from the Position, Position stakeholders and officials. To be able a good government system, each position as well as position holders in order to carry out its duties and functions in accordance with his position. So that all the planning, implementation and results in accordance with the objectives of the government. The empty position may create an unstable condition in the administration of government, therefore, the position must be filled by other officials, such as the replacement of public officials temporary. In Indonesian law the public officials temporary replacement is also called, executing the task (Plt. Pelaksana Tugas) or daily executor (Plh. Pelaksana Harian). Filling public positions temporary judged to be unable to government be effectively and efficiently. Because in some cases there is a weaknes (such as the power and authority) and resulted in double positions for officials. So the replacement officials temporary, such as executing tasks (Plt. Pelaksana Tugas) is not approriate method to create a system of good governance. Keyword : The effectiveness, the Positions, the replacement officials.